Summarizing application performance from a components perspective. - Srinivas, Kavitha (Software engineering notes.)
In the era of distributed development, it is common for large applications to be assembled from multiple component layers that are developed by different development teams. Layered applications have deep call paths and numerous invocations (average call stack depth of up to 75, and upto 35 million invocations in the applications we studied) making summarization of performance problems a critical issue. Summarization of performance by classes, methods, invocations or packages is usually inadequate because they are often at the wrong level of granularity. We propose a technique that uses thresholding and filtering to identify a small set of interesting method invocations in components deemed interesting by the user. We show the utility of this technique with a set of 7 real-life applications, where the technique was used to identify a small set (10-93) of expensive invocations which accounted for 82-99% of the overall performance costs of the application. Our experience shows that this type of characterization can help quickly isolate the specific parts of a large system that can benefit most from performance tuning.